2014
DOI: 10.3747/co.21.1741
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Pain and Anxiety in Rectal Cancer Patients During High-Dose-Rate Brachytherapy

Abstract: ful and painful for some. Insertion of the applicator was found to be the point of maximal pain, and medication was not always completely successful at alleviating the pain, suggesting that additional psychosocial interventions might be needed, with particular emphasis on the time of applicator insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This study found that the SAS and SDS scores in the experimental group were significantly lower than those in the control group after operation, and the difference was statistically significant (P<0.001); the SAS and SDS scores in the two groups after operation were significantly lower than those before operation, and the difference was statistically significant (P<0.001). The tension and anxiety of patients due to adverse reactions that might occur after operation can be relived by nursing intervention combined with early nutritional support, which could help patients' psychology, reduce negative emotions, and effectively alleviate their anxiety ( 18 , 19 ). According to literature reports, adverse reactions of early nutritional support were mainly characterized by nausea and vomiting, abdominal pain and abdominal distension, diarrhea and other symptoms ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the SAS and SDS scores in the experimental group were significantly lower than those in the control group after operation, and the difference was statistically significant (P<0.001); the SAS and SDS scores in the two groups after operation were significantly lower than those before operation, and the difference was statistically significant (P<0.001). The tension and anxiety of patients due to adverse reactions that might occur after operation can be relived by nursing intervention combined with early nutritional support, which could help patients' psychology, reduce negative emotions, and effectively alleviate their anxiety ( 18 , 19 ). According to literature reports, adverse reactions of early nutritional support were mainly characterized by nausea and vomiting, abdominal pain and abdominal distension, diarrhea and other symptoms ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low rectal cancer (i.e., any tumor lying <5 cm from the anal verge) is the most common type of rectal cancer ( 2 ), and it requires a complex treatment strategy based on surgery. Treatment, especially brachytherapy, adversely affects quality of life ( 3 ). Patients treated for low rectal cancer require a permanent stoma ( 4 ).…”
Section: Introductionmentioning
confidence: 99%